Design engineer's sourcebook - Richards, Keith L. (Taylor & Francis, CRC Press, 2018)
Design Engineer's Sourcebook provides a practical resource for engineers, product designers, technical managers, students, and others needing a design-oriented reference. This volume covers the mathematics, mechanics, and materials properties needed for analysis and design, with numerous examples. A wide range of mechanical components and mechanisms are then covered, with case studies interspersed to show real engineering practice. Manufacturing is then surveyed, in the context of mechanical design. The book concludes with information on clutches, brakes, transmission and other topics important for vehicle engineering. Tables, figures and charts are included for reference.